(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
Offshore pile foundations are essential for supporting structures, such as wind turbines, oil platforms, and bridges. Important factors influencing soil-pile interactions and assessing the impact of various environmental loads, including axial, lateral, and moment loads. This study begins with a comprehensive review of the analytical and numerical methods used for pile analysis. This research aims to analyze the behavior of piles in the offshore seabed environment, taking into account various factors, such as soil-pile interactions, environmental load conditions, and the design of a sturdy pile foundation. This research method exploits the importance of accurate modelling to ensure the stability and longevity of offshore structures. The strength and performance of offshore structures, such as wind turbines, oil platforms, and bridges, are highly dependent on the integrity of the pile foundations. This research will provide a detailed analysis of piles in offshore seabed environments, emphasizing the importance of soil-pile interactions, varying loading conditions, and robust pile designs. These findings underscore the need for an integrated approach that combines geotechnical data, advanced modelling, and ongoing monitoring to ensure the stability and longevity of offshore pile foundations. This research produces a foundational analysis of pile behavior in offshore environments, considering factors such as soil-pile interactions, environmental load conditions, and variations in pile diameter. Piles with a diameter of 1.067 m demonstrate the highest axial and lateral capacities, making them ideal for more extreme environmental load conditions, such as strong ocean currents and high wind loads.